Há diferenças significativas de qualidade no ensino superior brasileiro entre as modalidades Presencial e em Ead? - Barbosa, Murilo (Universidade do Vale do Rio dos Sinos, 2021)
Tis undergraduate project seeks to analyze the quality of Brazilian higher education, with the objective of identifying whether there are significant differences in the quality of higher education between the face-to-face and distance learning. Initially, it is necessary to analyze the Brazilian higher education structure and understand its current situation. In order to carry out a quality analysis, the courses of administration, accounting sciences, geography, Portuguese letters, mathematics and pedagogy in the South, Southeast and Center-West regions were selected and, based on the Enade Concept and explanatory variables of quality in teaching, a regression was estimated in order to verify the significance of the analysis of each course. From the use of the Data Envelopment Analysis (DEA) methodology in the significant courses, it was possible to identify the difference in quality of the modalities and a dispersion of the efficiency scores. The result was that in 45.83% of the analysed courses, the distance learning had a student quality inferior to face-to-face, the rest of the courses did not obtain any significant results.
Keywords: Ensino Superior; Análise Envoltória de Dados; EaD; Eficiência; University Education; Data Envelopment Analysis; Distance Learning; Efficiency